2016
DOI: 10.1186/s12931-016-0449-x
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil elastase cleaves epithelial cadherin in acutely injured lung epithelium

Abstract: BackgroundIn acutely injured lungs, massively recruited polymorphonuclear neutrophils (PMNs) secrete abnormally neutrophil elastase (NE). Active NE creates a localized proteolytic environment where various host molecules are degraded leading to impairment of tissue homeostasis. Among the hallmarks of neutrophil-rich pathologies is a disrupted epithelium characterized by the loss of cell-cell adhesion and integrity. Epithelial-cadherin (E-cad) represents one of the most important intercellular junction proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 55 publications
0
45
2
Order By: Relevance
“…We hypothesized that IL-17 induces FGF-2 production by bronchial epithelial cells. Surprisingly, as we found that FGF-2 production was impacted by a decrease in intercellular adhesion, rather than IL- 22,32 and pancreatitis. 33 Boxio et al 32 we also focused on E-cadherin/β-catenin signalling in bronchial epithelium and demonstrated that reduced levels of E-cadherin were associated with increased nuclear translocation of β-catenin in the Mix-in group.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…We hypothesized that IL-17 induces FGF-2 production by bronchial epithelial cells. Surprisingly, as we found that FGF-2 production was impacted by a decrease in intercellular adhesion, rather than IL- 22,32 and pancreatitis. 33 Boxio et al 32 we also focused on E-cadherin/β-catenin signalling in bronchial epithelium and demonstrated that reduced levels of E-cadherin were associated with increased nuclear translocation of β-catenin in the Mix-in group.…”
Section: Discussioncontrasting
confidence: 55%
“…Surprisingly, as we found that FGF-2 production was impacted by a decrease in intercellular adhesion, rather than IL- 22,32 and pancreatitis. 33 Boxio et al 32 we also focused on E-cadherin/β-catenin signalling in bronchial epithelium and demonstrated that reduced levels of E-cadherin were associated with increased nuclear translocation of β-catenin in the Mix-in group. Some previous reports showed that Wnt/β-catenin signalling is important for airway inflammation and airway remodelling 35 and for proteinase-mediated loss of cadherin.…”
Section: Discussioncontrasting
confidence: 55%
“…One reported mechanism involves proteolytic degradation of E-cadherin. E-cadherin degradation was observed during colonization of intestinal epithelium by enteric pathogens such as Bacteroides fragilis and Campylobacter jejuni [62, 63], or following neutrophil infiltration in the inflamed mucosa [64-66]. Invading bacteria and activated immune cells release different proteases that cause shedding of the E-cadherin ectodomain, thereby decreasing the concentration of adhesion competent protein at the plasma membrane.…”
Section: Regulation Of Aj and Tj Protein Expression In Inflamed Inmentioning
confidence: 99%
“…Briefly, mice were anesthetized by intraperitoneal (intraperitoneal) injection of ketamine hydrochloride (75 mg/kg) and medetomidine hydrochloride (1 mg/kg). Next, mice were challenged intranasally with 50 μL of saline buffer (PBS) containing a predetermined sublethal dose of bacteria (10 6 CFUs/ per mouse) [25]. Control mice (n = 5 mice/genotype) were challenged with 50 μL of sterile PBS alone.…”
Section: Bacteria and Intranasal Infectionmentioning
confidence: 99%